Alternative financing modes for higher learning institutions in Malaysia – Socially Responsible Investment (SRI) Sukuk & Social Impact Bonds (SIB) - Engku Ali, Engku Rabiah Adawiah; Hassan, Rusni; Kassim, Salina; Syed Azman, Syed Marwan Mujahid; Mohd. Zain, Nor Razinah (2018)
Higher learning institutions (HLIs) in Malaysia consists of 20 public universities and more than 500 private HLIs catering for an increasing number of student enrolments. Funding for HLIs has become increasingly constrained as the budget for the education sector has been seeing cuts in recent years. This gives rise to the ever-increasing concern on the issue of self-sustainability of HLIs. It is not an issue unique to Malaysia per se, but it is a global phenomenon where HLIs around the world have faced challenges in achieving self-sustainability. Central to this issue is the challenge to find sources of funds needed to sustain HLIs’ operations and development. This issue has been gaining increasing prominence especially when funds and resources are becoming lesser and limited as a result of the slowing growth of the global economy. It has, therefore, become a necessity for HLIs to come out with innovative ways to raise funds and move towards becoming more self-sustainable sooner rather than later. Possible lessons can be learned from HLIs in the UK, US, and Australia where universities have enriched their source of finance including their involvement in the capital market to raise funds through bonds. Funds are also raised through university-industry linkages from private grants and PPP projects. In the context of Malaysia, this paper focuses on exploring alternative financing modes for HLIs through Socially Responsible Investment (SRI) Sukuk and Social Impact Bonds (SIBs). The methods utilized in this study are a critical review of the literature, case study analyses and interview sessions with experts. Based on the findings, the study recommended 2 SRI Sukuk models: firstly, in the situation where the proceeds are used for income-generating activities, while secondly for non-income generating activities. The returns and repayments of the Sukuk are dependent on key performance indicators (KPIs) being achieved. In both cases, it is recommended that the Sukuk be issued by a consortium consisting of a number of different universities in order to lower the cost of issuance and fund management, as well as efficiently utilizing resources. It is also recommended that the Sukuk is guaranteed by a third party, preferably by the government.